Chronotopes and migration : language, social imagination, and behavior - Karimzad, Farzad; Catedral, Lydia (New York, NY : Routledge, 2021)
In Chronotopes and Migration: Language, Social Imagination, and Behavior, Farzad Karimzad and Lydia Catedral investigate migrants' polycentric identities, imaginations, ideologies, and orientations to home and host countries through the notion of chronotope. The book focuses on the authors' ethnographically situated research with two migrant populations - Iranians and Uzbeks in the United States - to highlight the institutional constraints and individual subjectivities involved in transnational mobility. The authors provide a model for how the notion of cultural chronotope can be applied to the study of language and migration at multiple scale levels, and they showcase a coherent picture of the ways in which chronotopes organize various aspects of migrant life. This book is a critical contribution to the conversation surrounding the sociocultural-linguistic uses of the chronotope, demonstrating its applicability not only to theorizing migration but also to theorizing language and social life more broadly.
OCLC-licensed vendor bibliographic record.
Keywords: Group identity; Immigrants -- Language -- Social aspects; Space and time in language; Sociolinguistics; Iranians -- United States; Uzbeks -- United States; LANGUAGE ARTS & DISCIPLINES / General